2018
DOI: 10.2174/1567205015666180119101832
|View full text |Cite
|
Sign up to set email alerts
|

AβPP-induced UPR Transcriptomic Signature of Glial Cells to Oxidative Stress as an Adaptive Mechanism to Preserve Cell Function and Survival

Abstract: Our study suggests that targeting oxidative and ER stress might be a potential therapeutic strategy against glia impairment in AMD and AD, in light of the common features between the two pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Glial cell activation is one of the pathological manifestations of AD ( 26 ). It has been suggested that the activation of glial cells may contribute to Aβ release ( 27 ), resulting in neuronal dysfunction and neuroinflammation, leading to the progression of AD ( 28 ). Immunohistochemistry staining results in the present study demonstrated that the increased Iba1 and GFAP expression in the hippocampus of 3xTg mice was reversed by SSD treatment, suggesting that microglia and astrocyte activation was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Glial cell activation is one of the pathological manifestations of AD ( 26 ). It has been suggested that the activation of glial cells may contribute to Aβ release ( 27 ), resulting in neuronal dysfunction and neuroinflammation, leading to the progression of AD ( 28 ). Immunohistochemistry staining results in the present study demonstrated that the increased Iba1 and GFAP expression in the hippocampus of 3xTg mice was reversed by SSD treatment, suggesting that microglia and astrocyte activation was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In response to ER stress, the MG exerts a protective role by upregulating AβPP to defend against apoptosis and recover functional gene transcription. 269 Interestingly, AβPP is proven to be harmful in neovascularization AMD, as mentioned before. These data seem to convey that AβPP is a dual regulator of cell survival dependent on VEGF expression level.…”
Section: Er Stress and Age-related Macular Degenerationmentioning
confidence: 78%
“…[266][267][268] These risk factors can induce ER stress in AMD models. [269][270][271] Research has revealed that different metabolic pathways, including the cholesterol pathway, retinoid metabolism, and lipid metabolism, are involved in drusen accumulation, neovascularization, and subretinal fibrosis via ER stress. We elaborate on the role of ER stress in the formation of AMD and its targeted treatment (Fig.…”
Section: Er Stress and Age-related Macular Degenerationmentioning
confidence: 99%
“…GRP78/BiP can also prompt the process of Müller cells, which are responsible for the retinal metabolism through the UPR, as shown in diabetic retinopathy. 60 , 61 Also, the activation and migration of Müller cells in LIRD have been confirmed to modulate the apoptotic loss of photoreceptor cells in the outer retina. 62 TEM in the present work also revealed that broadened Müller cell processes intervened in the space between photoreceptor somas, indicating metabolic modulation in the degenerative retina and engulfing and clearing of the damaged photoreceptor.…”
Section: Discussionmentioning
confidence: 97%